Envelhecimento bem-sucedido: uma análise dos fatores de proteção e vulnerabilidade - Crispim, Mônica Cristiane Moreira (2014)
This study aimed at estimating the psychosocial protective and vulnerability factors of successful aging. It was based on the premise that aging is a continuous process of multidimensional, multidisciplinary and heterogeneous dimensions which counts on factors of biological, psychological, social, cultural, economic types, as well as, coping, losses and gains facts. The research counted on a cross-sectional quantitative approach, 913 participants comprising, being divided into three studies. The first study used a sample of 288 elderly participants, was aimed to analyze the cross-cultural adaptation and psychometric properties of the Scale for Successful Aging (SAS), consisting of 14 items. The second study, counted on 270 elderly volunteers; it was aimed to analyze the cross-cultural adaptation and psychometric properties of the Brief Resilience Scale (BRS), consisting of six items. The third study consolidated the general purpose of investigating the protective and vulnerability factors of successful aging. To this end, it obtained a sample of 355 elderly volunteers who answered about 200 questions about successful aging, resilience, perceived stress, life satisfaction, anxiety, depression, health profile, as well as, socio demographic data. The first study presented a satisfactory results with an index of internal consistency α = 0.65 and the reduction of four items of the scale. The final version of SAS was composed of 10 items. The second study showed an internal consistency α = 0.78 and the factor structure of the scale maintained the number of the original items. The third study presented that BRS (β = 0.44, p <.01) and three of the other used scales [ESV (β = 0.38, p <.01); HADS-D (β = 0.38, p <.05); and PSN (β = 0.20, p <.01)] were predictors of protection or vulnerability of successful aging. The presented model is statistically significant [F (7, 35) = 17.59, p <.01)], accounting for 26% of the variance of successful aging. Therefore, this latter study showed, as protective factors, satisfaction with life, resilience, social support and better health perception, and as a vulnerability factor, the presence of depressive symptoms, and, for each construct, there are the determining factors and the supporting successful aging. Validation of multidimensional scaling SAS opens up several possibilities for future research, regarding the regional characteristics of successful aging in Brazil.